Coroner’s Preventive Role in Occupational and Industrial Calamities: A Fundamental Legal Review (International Seminar on Syariah and Law (INSLA), 2020)
This paper focuses on the coroner’s investigative role that relates to occupational death cases. Any death caused by industrial calamities occurred in the course of employment needs to be investigated thoroughly. The methodology used in this study is qualitative approach, which involves analysing data gathered through legislation, cases-law and official statistics; and comparative analysis with other jurisdictions. This research finds that the Malaysian occupational death investigation system needs to be reformed as the coronial institution is able to serve as an effective death investigator especially in giving recommendations for the prevention of future similar deaths.